Motivator and Challenges of Women Entrepreneurs - Iklima Husna Abdul Rahim; Noor Fzlinda Fabeil; Toh, Pei Sung (Journal of Global Business and Social Entrepreneurship, 2017)
Entrepreneurship is increasingly recognized as an important driver of economic growth, productivity, innovation and employment, and it is widely accepted as a key aspect of economic dynamism. The fast development in entrepreneurship has attracted women to join this field. Women did not miss the opportunity to jointly create a name in the industry and for those who want to succeed will be able to demonstrate the seriousness, willing to face challenges and the problems encountered. Women entrepreneurs will not be able to achieve success without high work, high morale and ability to face the challenges. Therefore, this conceptual paper will discuss the factors that influence women to become entrepreneurs, the challenges and problems faced by women entrepreneurs and suggestion to improve the potential and increasing of women’s success in entrepreneurship. Based on the literatures that have been made, there are several factors that have driven women entrepreneurs involved in entrepreneurship. Those are family support, family background, independent factors, interest, education, work experience, self-satisfaction, to achieve ambitions, motivation, to change family fortunes and other factors which are likely to become a source of income support for those involved in entrepreneurship. Therefore, the findings of this study are expected to assist women entrepreneurs to reduce the problems faced in the business.